(untitled) (Research, Society and Development, 2021)
The objective was to develop and verify the content validity and reliability of an instrument that proposes to assess the levels of food literacy in adolescents. The test and retest was conducted with 60 participants to estimate reliability. The instrument developed was called Adolescent Food Literacy (ALE). The content validity analysis was conducted by a team of experts. Then, the instrument reliability (Cronbach’s alpha/internal consistency) and test-retest (simple Kappa) were checked. After evaluation by the expert committee, the instrument was considered valid as to its content. Subsequently, it was recommended that the instrument be applied to evaluate the other proposed qualities. The results achieved were discussed again with the committee of experts, interviewers, and authors of the "LAA" instrument, who judged the instrument apt to be used in the remaining stages of the evaluations, with no need for changes, in the final version presented. The instrument was applied to 60 adolescents, of which 34 (56.7%) were male, with a mean age of 14.6 years and a prevalence of brown skin color/race (n=45 / 75%). With regard to the estimate of reliability, the internal consistency or Cronbach’s alpha estimated was 0.82. As for the reproducibility, it was verified that among the 54 questions of the instrument, only two obtained a Kappa lower than 0.60. Thus, the LAA instrument showed good application and easy understanding, good standards of reliability and content validity.